Successful Curative Cryoablation of an Esophageal Gastrointestinal Stromal Tumor. Issue 6 (June 2019) - Mai, Daniel; Hashimoto, Rintaro; Yu, Allen; Torralba, Ericson John; Tran, Elise; El-Hage Chehade, Nabil; Lee, David P.; Samarasena, Jason
Abstract : ABSTRACT: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. The most common location of GIST is the stomach; however, occurrences of GIST in the esophagus are also possible albeit rare. Although the current standard of care for gastric and intestinal GIST involves surgery and tyrosine kinase inhibitors, this case report focuses on the potential of treating esophageal GIST through a novel means of cryoablation therapy.